KETIMPANGAN PENDAPATAN DAN PENGELUARAN ANTARA MIGRAN DAN NON MIGRAN DI BANDA ACEH. - Khairida, Janna (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2016)
This study aims to determine how much revenue and expenditure inequality between migrants and non-migrants in Banda Aceh. Income inequality is a phenomenon that occurs in almost all countries in the whole world layers, either the poor countries, the developing countries, as well as developed countries, only that set it apart from all that is the level of inequality. Data used for this study are primary data, that are collected using questionnaires distributed by the three selected districts in the city of Banda Aceh. The data collected and processed by using Gini Ratio in which to determine the level of income and expenditure inequality between migrants and non-migrants in Banda Aceh produced and included into the category of being a resident migrants with GR = 0.42, while for the inequality of income for non-migrant included into the category of high with GR = 0.51. for the calculation of expenditure between migrants and non-migrants in Banda Aceh, migrant expenditures included into the medium category with GR = 0.41 and for non-migrant expenditures included into high category with GR = 0.51.Keywords: Migrant and Non-migrant Revenue, Expenditure and Non Migraines Migraines, Gini Ratio (GR)